2020
DOI: 10.1126/sciadv.abc1304
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic brain-to-brain concordance and behavioral mirroring as a mechanism of the patient-clinician interaction

Abstract: The patient-clinician interaction can powerfully shape treatment outcomes such as pain but is often considered an intangible “art of medicine” and has largely eluded scientific inquiry. Although brain correlates of social processes such as empathy and theory of mind have been studied using single-subject designs, specific behavioral and neural mechanisms underpinning the patient-clinician interaction are unknown. Using a two-person interactive design, we simultaneously recorded functional magnetic resonance im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 95 publications
(89 reference statements)
2
74
0
1
Order By: Relevance
“…With EEG-hyperscanning, Jahng et al [21] provided evidence in neural dynamics between dyads when nonverbal cues involving the rTPJ were adopted to predict opponents' intentions to cooperate or defect during the face-to-face prisoner's dilemma game. All the above-mentioned studies adopted either specialized analysis methods or additional cues, such as eye contacts [15] and facial co-analysis between patients and clinicians [26] in their analyses of the information flow. The common mechanism of interpersonal rapport triggering similar brain activities should be a common theme [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…With EEG-hyperscanning, Jahng et al [21] provided evidence in neural dynamics between dyads when nonverbal cues involving the rTPJ were adopted to predict opponents' intentions to cooperate or defect during the face-to-face prisoner's dilemma game. All the above-mentioned studies adopted either specialized analysis methods or additional cues, such as eye contacts [15] and facial co-analysis between patients and clinicians [26] in their analyses of the information flow. The common mechanism of interpersonal rapport triggering similar brain activities should be a common theme [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the coordinated or synchronized brain activation across people, i.e., intersubject correlation, was suggested as a mechanism of transmission of shared meaning and common interpretation that goes beyond cultural and linguistic boundaries (Honey et al, 2012): Moments of neural synchrony may be driven by shared attention to external stimuli in the environment or directly mediated by person-to-person communicative signals, through which interaction is conveyed (e.g., eye contact, facial expression, bodily gestures, vocal prosody). Correspondingly, the intersubjective oscillatory brain response has been related to empathic relationships and bonding (Wheatley et al, 2012;Hu et al, 2017), shown to be indicative of rapport (Ellingsen et al, 2020), emotion co-regulation and social learning, through mutual attention, and communication (Leong et al, 2017;Levy et al, 2017;Pratt et al, 2018;Reindl et al, 2018;Piazza et al, 2020). Recently, this implicit interpersonal neural resonance was suggested as the basis of attachment (Schore and Schore, 2008;Siegel, 2015;Long et al, 2020) and also affiliated with the development of resilience (Feldman, 2020).…”
Section: The Relational Brain and The Link Between Subjectivity And Intersubjectivitymentioning
confidence: 99%
“…Studien fant at smertelindringen ble formidlet gjennom pasient-terapeut-forholdet, nonverbal atferd og sosial speiling, som handler om å gi pasienten full oppmerksomhet gjennom for eksempel øyekontakt, stemmebruk og kroppsspråk (5). Funnene underbygger at sykepleiere kan fremme e ekten av medisinsk behandling gjennom et godt pasientforhold.…”
Section: Medisin Bør Administreres åPentunclassified